2018
DOI: 10.18632/oncotarget.25784
|View full text |Cite
|
Sign up to set email alerts
|

An intestinal stem cell niche in Apc mutated neoplasia targetable by CtBP inhibition

Abstract: C-terminal binding protein 2 (CtBP2) drives intestinal polyposis in the Apc min mouse model of human Familial Adenomatous Polyposis. As CtBP2 is targetable by an inhibitor of its dehydrogenase domain, understanding CtBP2’s role in adenoma formation is necessary to optimize CtBP-targeted therapies in Apc mutated human neoplasia. Tumor initiating cell (TIC) populations were substantially decreased in Apc min Ctbp2+/- intestinal epithelia. Moreover, normally nuclear Ctbp2 was mislocalized to the cytoplasm of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…5). For this purpose, we transfected expression plasmids encoding wt, G189A, W324F, and W324G-mutated CtBP2 cDNA into HCT116 cells homozygously deleted for CtBP2 using CRISPR techniques (Chawla et al, 2018). Intact transfected cells were then incubated with DSG at 37°C for 30 minutes, and total cellular protein was immunoblotted for CtBP2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5). For this purpose, we transfected expression plasmids encoding wt, G189A, W324F, and W324G-mutated CtBP2 cDNA into HCT116 cells homozygously deleted for CtBP2 using CRISPR techniques (Chawla et al, 2018). Intact transfected cells were then incubated with DSG at 37°C for 30 minutes, and total cellular protein was immunoblotted for CtBP2.…”
Section: Resultsmentioning
confidence: 99%
“…Cells [wild-type (wt) or CRISPR] were maintained according to the American Type Culture Collection's recommendation. HCT116; p53-/- (Straza et al, 2010), HCT116;CtBP2-/- (Chawla et al, 2018), and MDA-MB-231 cells were maintained in RPMI 1640 or Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% (v/v) FBS and penicillin-streptomycin, unless specified. Cells were maintained in a humidified incubator equilibrated with 5% CO 2 at 37°C.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Relative to a potential role for CtBP as a key oncogenic driver or dependency, our previous studies have shown that CtBP2 is a dependency for APC mutated neoplasia in the Min mouse intestinal polyposis model of human Familial Adenomatous Polyposis 23 . We further demonstrated that CtBP2 haploinsufficiency reduced tumor initiating cell (TIC) abundance in APC min/+ intestines, suggesting the oncogenic role of CtBP2 in intestinal neoplasia relates to its promotion of TIC activities 24 . These findings were more recently mirrored by similar findings in a mouse model of human pancreatic adenocarcinoma (PDAC), where CtBP2 deficiency slowed tumor growth, abrogated metastases, and severely attenuated expression of TIC markers 25 .…”
Section: Introductionmentioning
confidence: 87%